Hubungan Kecerdasan Emosional Dengan Coping Stress Dalam Belajar Siswa Kelas VIII SMPN 10 Kota Jambi - Sabrina Anjani; Akmal Sutja; Fellicia Ayu Sekonda (Departement of Mathematics Education, 2023)
In the teaching and learning process there are obstacles that are difficult for students to overcome which can cause stress in learning due to the inability of students to absorb or understand learning material at school, so that it requires appropriate stress coping strategies. The phenomenon of coping with stress in schools is the emergence of maladaptive student behavior such as difficulties in doing assignments, students often leave during class hours for no apparent reason, and create a noisy atmosphere in class. The purpose of this study was to determine the relationship between emotional intelligence and coping with stress in learning for class VIII students of SMPN 10 Jambi City. This type of research is quantitative research with correlational research methods. The sampling technique used simple random sampling with a total of 141 students as respondents. Analysis of research data using a correlation test with a significance level of 0.05. Retrieval of data in this study using the coping stress scale and emotional intelligence scale. The subjects of this study were class VIII students of SMPN 10 Jambi City. Data collection tools used are observation, interviews and questionnaires. This research was conducted by distributing questionnaires consisting of 35 items, namely 20 items of emotional intelligence and 15 items of coping with stress. The results of the reliability test on each scale are 0.750 on the coping stress scale and 0.800 on the emotional intelligence scale. The analysis technique used is pearson correlation. Pearson correlation test results obtained rxy = 0.506 with a significance level or p of 0.000. Because the p value < 0.05, the pattern of relationship between the variables of emotional intelligence and coping stress in class VIII students' learning is accepted, meaning that there is a relationship between the variables of emotional intelligence and coping stress in class VIII students